Urgensi Pendidikan Karakter dalam Membentuk Akhlak Mulia: Kajian Literatur Pendidikan Islam - Nur Fatimah; Cepi Budiyanto; Nu'man Ihsanda; Teguh Hariyanto; Aan Hasanah; Bambang Syamsul Arifin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The moral crisis occurring across various aspects of social life raises a fundamental question: how can education contribute to shaping individuals of noble character? In both global and national contexts, character education is increasingly viewed as a strategic solution to the ethical and behavioral degradation of students. This study aims to examine the urgency of character education from an Islamic perspective as a foundational element in the development of noble character. The method employed is a literature review, analyzing both classical and contemporary works from Islamic sources and general educational thought. The analysis focuses on the ideas of key figures such as Al-Ghazali, Ibn Miskawayh, as well as modern thinkers like Zakiah Daradjat and Thomas Lickona, using a descriptive-analytical approach. The main findings suggest that character education in Islam is not merely a moral instrument, but a path toward forming the insan kamil (complete human) through the integration of tawhid (divine unity), adab (proper conduct), and social ethics. This study distinguishes itself from previous research by emphasizing the integration of classical Islamic literature with modern character education theories in addressing contemporary ethical challenges. Although the study is conceptually based and lacks empirical validation, its theoretical implications provide a strong foundation for developing a contextually relevant moral education curriculum. The study affirms the importance of character education as the core of a holistic Islamic educational system capable of responding to today's moral crises.